1995
DOI: 10.1073/pnas.92.2.589
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of embryo freezing in mice.

Abstract: Embryo cryopreservation does not induce clear-cut anomalies at detectable rates, but several mechanisms exist for nonlethal damage during the freeze-thaw process, and the risk of moderate or delayed consequences has not been extensively investigated. In a long-term study including senescence, we compared cryopreserved and control mice for several quantitative traits. Significant differences were seen in morphophysiological and behavioral features, some of them appearing in elderly subjects. Thus, apart from it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(46 citation statements)
references
References 30 publications
1
43
0
2
Order By: Relevance
“…Nevertheless, it is known that these techniques induce changes in environ-mental and maternal side effects modifying the embryo gene expression and methylation pattern [19,20,36], the transcriptomic and proteomic placental profile [21], and their viability [29,37], but little is known regarding the long-term effects on the derived progeny. Some authors postulate that these procedures do not induce major anomalies but can lead to morphologic and behavioral features in adult mice derived from frozen embryos [16]. However, Auroux et al [17] found a beneficial effect in longevity in adults, and Lavara et al [22] reported a positive long-term effect on reproduction traits in rederived rabbit females from vitrified embryos, probably due to changes in epigenetic control regions related with reproductive traits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, it is known that these techniques induce changes in environ-mental and maternal side effects modifying the embryo gene expression and methylation pattern [19,20,36], the transcriptomic and proteomic placental profile [21], and their viability [29,37], but little is known regarding the long-term effects on the derived progeny. Some authors postulate that these procedures do not induce major anomalies but can lead to morphologic and behavioral features in adult mice derived from frozen embryos [16]. However, Auroux et al [17] found a beneficial effect in longevity in adults, and Lavara et al [22] reported a positive long-term effect on reproduction traits in rederived rabbit females from vitrified embryos, probably due to changes in epigenetic control regions related with reproductive traits.…”
Section: Discussionmentioning
confidence: 99%
“…anomalies but can lead to morphologic and behavioral features in adult mice derived from frozen embryos [16]. However, Auroux et al [17] found a beneficial effect in longevity in adults, and Lavara et al [22] reported a positive long-term effect on reproduction traits in rederived rabbit females from vitrified embryos, probably due to changes in epigenetic control regions related with reproductive traits.…”
Section: R Lavara Et Al / Theriomentioning
confidence: 99%
See 1 more Smart Citation
“…We did not find any obvious effect of culture when the offspring were subjected to a battery of preweaning developmental assays that included righting and grasp reflexes, cliff aversion, bar holding, growth rate, incisor appearance, and eyelid opening (23,24), suggesting that sensory and motor Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…However, the number of bucks and does necessary to produce one batch of embryos varies from one to three between populations. Later, we will have to address the problem of the size of the population that will produce the embryos and whether to store one (Glenister et al, 1990;Dulioust, 1995 …”
mentioning
confidence: 99%